2020
DOI: 10.1149/1945-7111/ab9e3e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effects of Chloride ions on Cyanide-Free Gold Electrodeposition

Abstract: It is very simple and convenient using the commercial chloroauric acid instead of sodium gold sulfite as the main salt in the Au(I) sulfite electrodeposition bath. In this paper, the effects of chloride ions on cyanide-free Au(I) electrodeposition in the gold sulfite bath are carefully investigated. Both UV-vis absorption spectroscopy and visual inspection reveal that chloride ions suppress the disproportionation reaction of Au(I) and improve the bath stability. Cyclic voltammetry indicates that chloride ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Therefore, sulfite is a suitable complexant for the cyanide-free electrodeposition of these metals. For the oxidation process, sulfite is inherently unstable and commonly oxidized to sulfate (SO 3 2– → SO 4 2– ). , However, studies on the cathodic process of sulfite are very limited. In our previous work, we first reported that sulfite first experienced a dimerization to metabisulfite, then followed an electroreduction to thiosulfate (SO 3 2– → S 2 O 5 2– → S 2 O 3 2– ) with the potential shifted negatively at a gold electrode/water solution interface . The intricate electrochemical reactions led to the adsorption of S 2 O 5 2– and S 2 O 3 2– on the cathode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sulfite is a suitable complexant for the cyanide-free electrodeposition of these metals. For the oxidation process, sulfite is inherently unstable and commonly oxidized to sulfate (SO 3 2– → SO 4 2– ). , However, studies on the cathodic process of sulfite are very limited. In our previous work, we first reported that sulfite first experienced a dimerization to metabisulfite, then followed an electroreduction to thiosulfate (SO 3 2– → S 2 O 5 2– → S 2 O 3 2– ) with the potential shifted negatively at a gold electrode/water solution interface . The intricate electrochemical reactions led to the adsorption of S 2 O 5 2– and S 2 O 3 2– on the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we first reported that sulfite first experienced a dimerization to metabisulfite, then followed an electroreduction to thiosulfate (SO 3 2− → S 2 O 5 2− → S 2 O 3 2− ) with the potential shifted negatively at a gold electrode/water solution interface. 25 The intricate electrochemical reactions led to the adsorption of S 2 O 5 27 Therefore, the suppression of sulfite dimerization and its subsequent electroreduction can not only elaborate the reaction mechanism of sulfite at the solid/water interface but also provide a practical guidance for the metal electrodeposition.…”
Section: ■ Introductionmentioning
confidence: 99%